2003
DOI: 10.1021/ja034015j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3-Hydroxyproline Residues on Collagen Stability

Abstract: Collagen is an integral part of many types of connective tissue in animals, especially skin, bones, cartilage, and basement membranes. A fibrous protein, collagen has a triple-helical structure, which is comprised of strands with a repeating Xaa-Yaa-Gly sequence. l-Proline (Pro) and 4(R)-hydroxy-l-proline (4-Hyp) residues occur most often in the Xaa and Yaa positions. The 4-Hyp residue is known to increase markedly the conformational stability of a collagen triple helix. In natural collagen, a 3(S)-hydroxy-l-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
141
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(153 citation statements)
references
References 38 publications
11
141
0
1
Order By: Relevance
“…For bovine ␣1(V) sequences, a BLAST search of bovine genome databases using human pro-␣1(V) sequences (44) identified mRNA sequence XM_002691720.1, predicted by automated analysis of genomic sequences, which encodes the pro-␣1(V) C-propeptide and ϳ38% of the ␣1(V) major triple helical (COL1) domain interspersed with gaps and insertions of non-␣1(V) sequences probably due to annotative misidentification of intron/exon junctions. Toward obtaining complete bovine ␣1(V) COL1 sequences, first strand cDNA was synthesized from bovine placenta total RNA (Zyagen, San Diego, CA) using oligo(dT) 20 primers. Primers 5Ј-AGGCCCCCCAGGCGAGGTC-3Ј (forward) and 5Ј-ATTCTGGCCCCTTCAGACTT-3Ј (reverse), based on XM_002691720.1 COL1 sequences, were then used to amplify an ϳ1.8-kb fragment of COL1 sequences that was directly sequenced using the same forward primer.…”
Section: ␣1(v)mentioning
confidence: 99%
See 1 more Smart Citation
“…For bovine ␣1(V) sequences, a BLAST search of bovine genome databases using human pro-␣1(V) sequences (44) identified mRNA sequence XM_002691720.1, predicted by automated analysis of genomic sequences, which encodes the pro-␣1(V) C-propeptide and ϳ38% of the ␣1(V) major triple helical (COL1) domain interspersed with gaps and insertions of non-␣1(V) sequences probably due to annotative misidentification of intron/exon junctions. Toward obtaining complete bovine ␣1(V) COL1 sequences, first strand cDNA was synthesized from bovine placenta total RNA (Zyagen, San Diego, CA) using oligo(dT) 20 primers. Primers 5Ј-AGGCCCCCCAGGCGAGGTC-3Ј (forward) and 5Ј-ATTCTGGCCCCTTCAGACTT-3Ј (reverse), based on XM_002691720.1 COL1 sequences, were then used to amplify an ϳ1.8-kb fragment of COL1 sequences that was directly sequenced using the same forward primer.…”
Section: ␣1(v)mentioning
confidence: 99%
“…To obtain the remaining bovine ␣1(V) COL1 sequences, forward primer 5Ј-GTGGCACAGAATTGCTCTCA-3Ј, based on XM_617549.3 sequences, was used with primer 5Ј-GCC-TTCACTGCCTTTCAGTC-3Ј (reverse primer A) based on XM_002691720.1 sequences to amplify a ϳ2.7-kb fragment. The ϳ2.7-kb fragment could not be amplified from first strand cDNA synthesized using oligo(dT) 20 primers as above and was instead amplified from first strand cDNA obtained using reverse primer A. The ϳ2.7-kb PCR fragment was directly sequenced sequentially using reverse primers 5Ј-GTGGCACA-GAATTGCTCTCA-3Ј, 5Ј-CTCCAAGTTTGCCCTTCTCC-3Ј, and 5Ј-GCCCCTTTCTCCGTCTTC-3Ј.…”
Section: ␣1(v)mentioning
confidence: 99%
“…There is good evidence that aggregates of aligned procollagen molecules exit the Golgi (38), and aggregates appear to be a better substrate for BMP-1, the procollagen C-propeptidase, than individual procollagen molecules (39). Initial studies with synthetic peptides suggested a possible destabilization of the triple helix by 3Hyp (40), but further work concluded a marginal added stability (41). The crystal structure of a synthetic peptide containing 3Hyp and a Gly-Xaa-Xaa repeat showed that the 3-OH on proline pointed out from the triple helix and so could mediate hydrogen bonding to other protein molecules (42).…”
mentioning
confidence: 99%
“…P3H2 was initially identified as a protein mainly localised to the endoplasmic reticulum and Golgi (Jarnum et al, 2004), but more recently has been demonstrated in tissues rich in basement membranes, and participates in the hydroxylation of collagen IV (Tiainen et al, 2008). It has previously been hypothesised that prolyl 3-hydroxylation occurs after prolyl 4-hydroxylation, thus once the triple helix is formed, the 3-hydroxyproline results in destabilisation (Jenkins et al, 2003;Mizuno et al, 2004). There are no published reports on the function of P3H3.…”
mentioning
confidence: 99%